From gym to joy: The serial mediation of motor competence and health literacy in Chinese university students’ exercise-life satisfaction pathway - Shao-Shuai Ma; Zhe Zhu; Dongsheng Cai; Chen-Xi Li; Ya-Xing Li; Bo Li; Sai Zhu; Jiaxian Geng (PLoS ONE, 2025)
Purpose To investigate the impact of exercise adherence on life satisfaction among Chinese university students and to explore the mediating roles of motor-skill competence and health literacy. The ultimate goals are to provide a comprehensive understanding of the mechanisms underlying the relationship between physical activity and well-being, and to inform the development of targeted interventions that promote holistic student development. Method A total of 15,031 valid responses were extracted from a national university-student survey database. All variables were assessed with standardized questionnaires. Data were analyzed with SPSS 27.0. Promoting the physical and mental well-being and holistic development of students has become a policy priority that commands national attention, public concern, and sustained governmental focus, and the PROCESS macro v4.0. Result Exercise adherence, life satisfaction, motor-skill competence, and health literacy were positively intercorrelated. Exercise adherence significantly and positively predicted university students’ life satisfaction. The indirect effect along Path 1—exercise adherence → motor-skill competence → life satisfaction—was 0.003, accounting for 1.1% of the total effect. The indirect effect along Path 2—exercise adherence → health literacy → life satisfaction—was 0.067, accounting for 26.25% of the total effect. The indirect effect along Path 3—exercise adherence → motor-skill competence → health literacy → life satisfaction—was 0.001, accounting for 0.28% of the total effect. Conclusion The study findings reveal that exercise adherence has a positive direct effect on university students’ life satisfaction and also exerts an indirect effect through the sequential mediation of motor-skill competence and health literacy. These results provide empirical evidence of the complex interplay between physical activity, skill development, and mental health.